PH-Sensitive polymer assisted self-aggregation of bis(pyrene) in living cells in situ with turn-on fluorescence. (6th August 2015) - Duan, Zhongyu; Gao, Yu-Juan; Qiao, Zeng-Ying; Qiao, Shenglin; Wang, Yongmei; Hou, Chunyuan; Wang, Lei; Wang, Hao
Abstract: Supramolecular self-assemblies with various nanostructures in organic and aqueous solutions have been prepared with desired functions. However, in situ construction of self-assembled superstructures in physiological conditions to achieve expected biological functions remains a challenge. Here, we report a supramolecular system to realize the in situ formation of nanoaggregates in living cells. The bis(pyrene) monomers were dispersed inside of hydrophobic domains of pH-sensitive polymeric micelles and delivered to the lysosomes of cells. In the acidic lysosomes, the bis(pyrene) monomers were released and self-aggregated with turn-on fluorescence. We envision this strategy for in situ construction of supramolecular nanostructures in living cells will pave the way for molecular diagnostics in the future.